The Ornament of the Malay Keris Hulu “Tumbuk Lada” as a Medium for Student Creativity in Fine Arts - Azis, Adek Cerah Kurnia; Azmi, Azmi; Saleh, Khaerul; Tarigan, Nelson; Purba, Rinanda; Mesra, Mesra; Yumielda, Vivi Destri (V-art: Journal of Fine Art, 2025)
This study aims to develop and evaluate teaching materials in the form of printed books and e-books for the Ornamen Nusantara course, focusing on the ornamental design of the Hulu Keris Melayu Tumbuk Lada. The development process employed the Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate). The results indicate that the teaching materials are valid (78,75%), practical (82,15%), and effective (88,53%). Their use has been shown to enhance students’ understanding of traditional ornamental richness; particularly the Melayu Tumbuk Lada ornament; and to encourage the preservation of local cultural values. More broadly, the findings contribute to strengthening cultural identity in art education and support the development of creative industries based on cultural heritage.